Transesterification Kinetics of Jatropha Methyl Ester and Trimethylol propane for Biolubricant Synthesis Using Paphiaundulata Shell Waste - Said, N.; Misebah, Fatimah A.; Siti F., Haron; R. M., Yunus (AENSI, 2015)
Indium tin oxide (ITO) thin films of 150 nm thickness were deposited on quartz glass substrates by RF sputtering technique, followed by thermal annealing treatment. In this technique, the samples have been annealed at different temperature, 300ᴼC, 400ᴼC, 500ᴼC respectively in Argon gas flow. Structural and surface morphological properties were analyzed by X-ray diffraction (XRD) and Atomic Force Microscopy (AFM) after annealing. The XRD showed a polycrystalline structure of ITO film with maximum peak intensity at 2θ= 30.54, <222> orientation without any change in the cubic structure. Continuous and homogeneous films obtained by the AFM after annealing treatment. The visible spectrum from the spectrophotometer showed high transparency between 81% and 95% in the. Increasing the annealing temperature yields evenly distributed pyramidal peaks shaped particles with low roughness. Resistance of ITO thin film was significantly improved from 8.75 kΩ to 1.96 kΩ after 10 minute from 300ᴼC to 500ᴼC annealing temperatures respectively under Argon gas flow. ITO films physical properties would be well improved by this method which is highly suitable for cost effective photonic devices.